The comparative effect of FUV, EUV and X-ray disc photoevaporation on gas giant separations. Issue 3 (18th April 2018) - Jennings, Jeff; Ercolano, Barbara; Rosotti, Giovanni P
Abstract: Gas giants' early (≲5 Myr) orbital evolution occurs in a disc losing mass in part to photoevaporation driven by high energy irradiance from the host star. This process may ultimately overcome viscous accretion to disperse the disc and halt migrating giants by starving their orbits of gas, imprinting on giant planet separations in evolved systems. Inversion of this distribution could then give insight into whether the stellar FUV, EUV or X-ray flux dominates photoevaporation, constraining planet formation and disc evolution models. We use a 1D hydrodynamic code in population syntheses for gas giants undergoing Type II migration in a viscously evolving disc subject to either a primarily FUV, EUV or X-ray flux from a pre-solar T Tauri star. The photoevaporative mass loss profile's unique peak location and width in each energetic regime produces characteristic features in the distribution of giant separations: a severe dearth of ≲2 M J planets interior to 5 au in the FUV scenario, a sharp concentration of ≲3 M J planets between ≈1.5–2 au in the EUV case and a relative abundance of ≈2–3.5 M J giants interior to 0.5 au in the X-ray model. These features do not resemble the observational sample of gas giants with mass constraints, although our results do show some weaker qualitative similarities. We thus assess how the differing photoevaporative profiles interact with migrating giants and address the effects of large model uncertainties as a step to better connect disc models with trends in the exoplanet population.